UANG PALEPOH AMBUN DALAM PERKAWINAN DI TABEK PATAH KABUPATEN TANAH DATAR MENURUT PERSPEKTIF HUKUM ISLAM - Tarmizi Taher; Zulkifli Zulkifli (Jurnal Integrasi Ilmu Syariah (Jisrah), 2022)
This study examines palepoh ambun money in marriage and the view of Islamic law on the implementation of palepoh ambun money in marriage in Nagari Tabek Patah, Tanah Datar Regency. This research is empirical qualitative research. The data was obtained through interviews with community leaders, Alim Ulama, Niniak mamak, the chairman of KAN, and the perpetrators of the ambun palepoh money. The findings of this study are that if there is a man outside or from another village who wants to marry a woman from the Tabek Patah village, the man must pay palepoh ambun money. The urgency of the palepoh ambun money is to support the smooth running of the marriage process because the money is to ease the transportation costs of ninik mamak in the marriage process, according to the term bajalan baaleh tapak, bakato baaleh lidah, because ninik mamak and tribal chiefs are not paid in Minangkabau customs so they are not paid may be using personal money, not only that the money is also used for the cost of entertaining the men's family. According to Islamic law, palepoh ambun money is not a requirement related to marriage. Therefore, palepoh ambun money does not conflict with syara' law. This tradition of palepoh ambun money contains beneficial values in the form of reducing the cost of ninik mamak, strengthening the friendship between mamak of both parties, and easing the cost of the kitchen, so that the payment of palepoh ambun money is permissible (permissible), meaning that it can be carried out by the community as long as it fulfills the elements of 'Urf sahih, which is beneficial and does not cause harm.